Challenges of Teaching Poetry at Secondary Level: Perspectives from Nepalese English Teachers - Chaudhary, Shuva Lal; Karki, Tek Mani; Karki, Bishal; Pandey, Shiv Ram (Dristikon: A Multidisciplinary Journal, 2026)
The current research has discussed the challenges associated with teaching poetry in secondary school in Nepal among English teachers. The study utilized a qualitative research design and employed a narrative inquiry as the method of data collection, involving interviews, recordings, and diary notes. Ten community secondary schools in Kathmandu Metropolitan City were selected through purposive sampling, and one English teacher of each school was interviewed. Data were interpreted using thematic analysis. The results showed that the teachers have faced major linguistic problems, such as problems with archaic words, lexical and semantic complexities, figurative language, and odd syntactic structures. Cultural issues also came up as they reflected barriers to do with societal norms, traditions and values, and the cognitive issues were associated with understanding and interpretation of poetic forms. The respondents emphasized that it is especially challenging to teach poetry in the classroom, and the most common approach to teaching poetry in community schools is translation. The paper highlights the importance of contextually sensitive pedagogical approaches, teacher development, and curriculum-scaffolding to mitigate such factors and improve student engagement and comprehension of poetry.